Análise da cobertura do Google news: um estudo comparativo de Brasil, Colombia, México, Portugal e España - Cordeiro, Douglas Farias (2024)
This study aims to examine the news coverage provided by Google News across five Ibero-American countries, including three from Latin America and two from Europe: Brazil, Colombia, Mexico, Portugal, and Spain. The main focus is to highlight the differences and similarities in news presentation within diverse contexts, evaluating the presence and distribution of news using quantitative indicators, and analyzing the predominant content in each country’s news, based on a dataset collected between January 2 and January 31, 2024. This includes examining news sources, geographic coverage, prominent figures, and the prevalence of sensational elements through the identification of clickbaits. Our research employs statistical analyses and algorithmic solutions in natural language processing and artificial intelligence to generate results. The analyses revealed consistency in the daily delivery of content by Google News, with specific variations in the update rate across the studied countries. A diversity of news sources was observed, with a greater tendency toward local news and frequent mentions of politicians, celebrities, and businesspeople. In addition, the analyses uncovered a significant presence of clickbait, with variations across the countries and topics.